Physiological quality of chia seeds as a function of coat color and fungicide treatment - Roque Benetoli da Silva, Tiago (2024)
Chia (Salvia hispanica) seeds have attracted great economic interest for their high levels of linoleic and α-linolenic acids. In Brazil, there is a lack of studies on the agronomic characteristics and physiological quality of chia, necessitating research on germination processes and strategies to enhance yield under field conditions. There are no studies assessing the development of seeds with different coat colors in the presence of fungicides. This study aimed to assess the physiological quality of chia seeds as a function of coat color and fungicide treatment. For this, seeds were divided into two groups according to coat color (white and black) and subjected or not to treatment with carboxin + thiram. Germination speed index, germination rate, and shoot length were evaluated in plants sown at 0, 90, and 180 days after seed treatment. Germination rate and speed index differed significantly between coat colors, with white seeds having higher vigor than black seeds. Shoot length, however, differed only for seeds sown on the day of treatment, indicating that treated seeds were more vigorous.